MYSIR 2022 Virtual E-Abstract 2 - Interventional Radiology, Malaysian Society of (The Interventionalist Journal, 2022)
1. A RED HERRING OF MEDIASTINAL LYMPHOMA 2. ACUTE SUBMANDIBULAR SIALADENITIS; A RARE COMPLICATION POST POSTERIOR FOSSA SURGERY 3. A COST ANALYSIS OF INTERVENTION RADIOLOGY RELATED PROCEDURES IN VASCULAR ACCESS FOR HEMODIALYSIS 4. A CASE SERIES OF SPONTANEOUS EXTRAPERITONEAL HEMORRHAGE IN COVID-19 PATIENTS IN MALAYSIA 5. CONCURRENT STENTING OF MALIGNANCY-RELATED SVC & PULMONARY ARTERY STENOSES : A CASE REPORT